Addition Reaction between Piperidine and C60 to Form 1,4-Disubstituted C60 Proceeds through van der Waals and Dative Bond Complexes: Theoretical and Experimental Study - Lo, Rabindranath; Manna, Debashree; Lamanec, Maximilián; Wang, Weizhou; Bakandritsos, Aristides; Dračínský, Martin; Zbořil, Radek; Nachtigallová, Dana; Hobza, Pavel (Journal of the American Chemical Society, 2021)
A combined computational and experimental study reveals the character of the C60 complexes with piperidine formed under different reaction conditions. The IR and NMR experiments detect the dative bond complex, which according to NMR, is stable in the oxygen-free environment and transforms to the adduct complex in the presence of O2. Computational studies on the character of reaction channels rationalize the experimental observations. They show that the piperidine dimer rather than a single piperidine molecule is required for the complex formation. The calculations reveal significant differences in the dative bond and adduct complexes' character, suggesting a considerable versatility in their electronic properties modulated by the environment. This capability offers new application potential in several fields, such as in energy storage devices.